Jinayah Classification Based on Hadith - Siti Azizi Z Matondang; Hisam Ahyani (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
This study aims to analyze the classification of jinayah in Islamic criminal law based on the hadith as the second source of law after the Qur'an. Jinayah is a criminal act that harms the soul, body, or human honor. This study uses a descriptive qualitative approach by examining the hadith literature and the views of Islamic jurisprudence scholars. The results of the study indicate that jinayah is divided into three main categories, namely hudud jinayah, qishash-diyat, and ta'zir. Hudud jinayah is a criminal act with sanctions that have been clearly determined in the Qur'an and hadith and cannot be changed. Qishash-diyat jinayah relates to violations against the soul and body with sanctions in the form of retribution or diyat that can be forgiven by the victim or heirs. Meanwhile, ta'zir jinayah is a criminal act whose sanctions are not explicitly determined in the texts and are left to the discretion of the judge or ruler. The differences between the three lie in the source of legal determination, the nature of the sanctions, and the authority in imposing punishment. Thus, the classification of jinayah based on hadith shows the flexibility and firmness of Islamic law in maintaining justice and the benefit of society.